Children’s influence over family food purchases of ultra processed foods: interference of nutritional status - Tailane Scapin; Caroline Camila Moreira; Giovanna Medeiros Rataichesck Fiates (O Mundo da Saúde)
The difference was not statistically significant, but indicates a tendency, suggesting that parents are finding it difficult to refuse their children’s requests. Actions to inform and guide parents on the influence of children on their food shopping would be valuable to instrument them on how to deal with the situation. Children act as a person who influences consum- ers directing their parents’ choices towards the purchase of foods for their own intake. Among the most requested foods are the ultra processed ones, with high energy density, high fat, sugar and fat content, and low fiber content. Increased ingestion of such foods, together with low levels of physical activity, explains, in part the growing of the prevalences of child overweight and obesity observed in the last decades. The study’s objective was to investigate de influence of children over their parents’ food shopping, and relate this to their nutritional status. The transversal quali-quantitative study was carried out among 187 parents conducted from 7 to 10 year old students enrolled in public schools of Florianópolis / SC, in 2001. Surveys were sent to parents and anthropometric measures were obtained from children to evaluate nutritional status. Results showed that nearly one third (32.6%) of the students were overweight. From the 187 parents, 181 referred buying foods at their children’s request, and those whose children were overweight did it more frequently (result not significant). Parents mentioned 446 foods as the most requested by their children. 84.3% of which were classified as ultra processed. Parents of students with excessive weight reported that their children asked 23% more ultra processed foods than those parents whose children were not overweight. The difference was not statistically significant, but indicates a tendency, suggesting that parents are finding it difficult to refuse their children’s requests. Actions to inform and guide parents on the influence of children on their food shopping would be valuable to instrument them on how to deal with the situation.